Cylindrical shells under uniform bending in the framework of Reference Resistance Design. (March 2020) - Wang, Jie; Fajuyitan, O. Kunle; Orabi, M. Anwar; Rotter, J. Michael; Sadowski, Adam J.
Abstract: The resistance of cylindrical shells and tubes under uniform bending has received significant research attention in recent times, with a number of major projects aiming to characterise their strength through both experimental and numerical studies. However, the investigated cross-section slenderness ranges have mostly addressed low radius to thickness ratios where buckling occurs after significant plasticity and the influence of geometric imperfections is relatively minor. The behaviour under uniform bending of thinner imperfection-sensitive cylinders that fail by elastic buckling was largely omitted, as was the influence of finite length effects. The value of such resistance models that are only useful for thicker cylinders is therefore somewhat limited. This paper offers the most comprehensive known characterisation of the buckling and collapse resistance of isotropic cylindrical shells and tubes under uniform bending. Expressed within the modern framework of Reference Resistance Design (RRD), it holistically incorporates the effects of material plasticity, geometric nonlinearity and sensitivity to realistic and damaging weld depression imperfections. The characterisation was made possible by the authors' recently-developed novel methodology for mass automation of nonlinear shell buckling finite element analyses. A modification of the RRD formulation is proposed which facilitates its application to systems of low slenderness, and offers a compact algebraic characterisation of all potential imperfection amplitudes for this common shell structural condition. A reliability analysis is also performed. Highlights: Comprehensive computation exploration of cylindrical shells under uniform bending Length-dependent plasticity, buckling and imperfection sensitivity relationship explored Closed-form algebraic characterisation offered for entire range of behaviours. Enhancement to Reference Resistance Design to account for imperfect thick shell behaviour EN 1990 Annex D reliability analysis performed, with critique of underlying tests database.